Role of HLA-DRB1*13 Allele as a Recovery Factor Among Acute Hepatitis B than Chronic Hepatitis B Infected Patients: A Comparative Study from Bangladesh (Bangladesh Journal of Infectious Diseases, 2020)
Background: The course of hepatitis B virus (HBV) infection is not only determined by variations in viral virulence but may be influenced by host immune response, where Human Leukocyte Antigen (HLA) plays an important role.Objective: The purpose of the present study was to explore whether HLA-DRB13* allele of MHC gene had any influence in spontaneous recovery from HBV infection among Bangladeshi adults.Method: This cross sectional study was carried out at the Department of Virology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka Bangladesh. A total of 90 randomly selected hepatitis B virus infected adult patients, consisting of 30 acute HBV infections, 30 chronic HBV infection and 30 healthy controls were selected according to selection criteria for evaluation of HLA DRB1*13 allele. Detection of HLA DRB1*13 allele was done by conventional PCR followed by agarose gel electrophoresis.Result: The study revealed a significant increase of DRB1*13 in acute hepatitis B (AHB vs HC-40% vs 6.7%, RR= 9.4; P value